Simulation of the ignition mechanisms of low and high octane number blended fuels in HCCI engine - Munthanna, Jamil; Mohd Adnin, Hamidi; Ahmad Fitri, Yusop; Muhammad Anas, Abdul Aziz; Mohamad Fathin, Hamidi; Sundram, Tatchineswaranpillai (IOP Publishing, 2020)
Homogenous Charge Compression Ignition (HCCI) is an alternative combustion concept for in reciprocating engines which offers significant benefits in terms of its high efficiency and low emissions. HCCI is the most commonly used name for the auto-ignition of various fuels and one of the most promising alternatives to SI and CI combustion. This study focus on the ignition reactions of low and high octane number of fuel blends through comprehensive simulation. This study was carried out by using n-heptane as a base fuel and toluene as a sub fuel use as a fuel mixture in this simulation. Furthermore, for numerical analysis, MATLAB Software has been used to design simplified model of reaction mechanism for n-heptane. The simplified model has been discussed in this study. The highest value of hydroxyl radicals OH was achieved at approximately 0.23 at NTF 10 (Toluene mixture 10%) and the line decreased until 0 This value is gradually decreased when the mixture of toluene (NTF) as sub fuel is elevated until NTF60 Due to the content percentage of toluene added 10% consecutively, HCHO production increased as well. It is because HCHO consumes OH and at the same time affects the amount of OH. By doing this method (mixing n-heptane with toluene), the ignition delay of the fuel becomes longer is described. It is also shows that the simplified model constructed with a consideration of the property of reaction happen in nheptane (base fuel) added with toluene (sub fuel) in which OH reproduction and fuel + OH reaction plays important role. The purpose of this study is to figure out the reaction mechanism of compression ignition at Low Temperature Oxidation (LTO) and design the simplified model of reaction mechanism for n-heptane + toluene (NTF).